A Minority in the Making: The Shia Muslim Community in Norway - Bøe, Marianne 1977-; Flaskerud, Ingvild 1962- (2017)
In this article, we document and discuss transnational links and localising dynamics that are relevant for a young Shia community in the making in Norway. The Shia community is a minority in the Muslim minority population of Norway, and has been an almost neglected field of research. With this article we therefore aim to add knowledge to this field. First we provide an overview of the development of Shiism in Norway, and then we examine what kind of dynamics have come to the fore in ritual practice and in shaping a Norwegian Shia Muslim identity, through institutionalisation, knowledge, production and visibility.
Keywords: Shiism -- Norway -- localisation -- transnationalism -- identity -- ritual practice